Occurrence of Helicobacter pylori in drinking water sources and antimicrobial resistance profile in the central region of Peru - María Custodio; Raúl Montalvo-Otivo; Jhonatan Crispín-Ayala; Jeampier Bendezu-Meza; Pilar Herrera-Quintana; Heidi De la Cruz; Javier Huarcaya (Heliyon)
Introduction: Contamination of drinking water by Helicobacter pylori can cause serious diseases, including cancer. The determinants of the infection rate are socioeconomic status, low standard of living and overcrowding. In addition, exposure to environmental sources contaminated with feces, such as water and vegetables, is another risk factor for infection. We analyzed the occurrence of H. pylori in drinking water sources and the antimicrobial resistance profile in central Peru. Methods: Water samples were collected from taps in four provinces of the Junín region. Previously, biofilm sampling was performed from the internal surface of the taps. The samples were cultured on modified brain heart infusion blood agar at 37 °C under microaerophilic conditions for seven days. Antibiotic sensitivity of H. pylori was determined by the Kirby Bauer diffusion method. Results: The results revealed that pH (9.25) and turbidity (5.15 NTU) exceeded the Peruvian environmental quality standards for drinking water. The amount of free chlorine residual in the H. pylori positive water samples ranged from 0.02 to 0.12 mg/L. H. pylori was present in 2/192 tap water samples (1.04 %) and in 3/192 tap biofilm samples (1.56 %). It was observed that 100 % of H. pylori isolates from water samples from the Chilca district showed resistance to nalidixic acid and 66.67 % to both amoxicillin and chloramphenicol. Resistance to nalidixic acid of H. pylori isolates obtained from biofilm samples from taps in the El Tambo district ranged from 66.67 % to 100 %. Conclusion: The study findings reveal that water samples and tap biofilms in the Chilca, El Tambo and Huamancaca chico districts in the Junín region harbor H. pylori. They also reveal variability in the pattern of resistance to more than one antibiotic tested from one district to another.